Risk and human rights in UK prison governance - Murphy, Thérèse; Whitty, Noel (Oxford University Press, 2007)
Risk and human rights discourses dominate the landscape of prison governance in the United Kingdom. For the most part, however, criminologists have focused only on concepts of risk and lawyers on human rights; there has been little overlap in the scholarship of these disciplines. In this article, we problematize this separation. We argue for a new stream of academic enquiry which recognizes the co-existence of different types of risk and rights discourses, and which draws upon more interdisciplinary understandings of risk, human rights and regulation.